Characterization of resveratrol content in ten wild species of section Arachis, genus Arachis - Lopes, Renata Miranda; Silveira, Dâmaris; Gimenes, Marcos Aparecido [UNESP]; Vasconcelos, Paula Andreia S. [UNESP]; Alves, Rosa de Belem N.; Silva, Joseane Padilha; Agostini-Costa, Tânia da Silveira (Springer Nature, 2013)
Peanut is one of the few plants that synthesizes resveratrol, a phenolic compound of the stilbene class, which has been associated with reduced risk of developing chronic diseases, such as cancer, cardiovascular diseases, skin diseases, pulmonary diseases, diabetes and neurological diseases. Resveratrol was detected in different parts of the peanut plant, including roots, leaves, seeds and their derivatives. The wild species of the Arachis section are also strong candidates to synthesize resveratrol because they are phylogenetically closely related to cultivated peanut. Our objective was to characterize the resveratrol content in ten wild species of Arachis with three different genomes (A, B and K). The plant material was composed of leaves of the ten species treated (test) and not treated (control) with ultraviolet (UV) radiation. The test and control samples were extracted and the identification and quantification of resveratrol was performed using high performance liquid chromatography (HPLC). All species studied synthesized resveratrol and the concentrations ranged from 299.5 μg/g in A. kempff-mercadoi to 819.9 μg/g in A. cardenasii. DPPH antioxidant activity varied between 18.7 % for A. duranensis and 48.2 % in A. simpsonii. The results showed that wild Arachis species are a potential source of alleles for improvement of cultivated peanut, with the aim of achieving higher resveratrol content in leaves. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Antioxidant; Fabaceae; Peanut; Stilbene; Wild Arachis